Ecofisiologia de cryptostegia madagascariensis Bojer ex Decne submetida à restrição hídrica - Saraiva, Jose Gidalto Oliveira (2016)
The introduction of exotic species in natural communities is usually mediated by human activity. One example is Cryptostegia madagascariensis, species considered invasive in almost every country in which it was introduced. In Brazil, it is invading wetlands in the Northeast and is known as the Carnaubeiras (Copernicia prunifera) killer. The species is highly tolerant to flooding, but it also has drought tolerance. It is necessary to understand how adaptation to drought occurs, to identify the capacity of this plant to invade new areas. The objective of this work is to understand the adaptation of C. madagascariensis to low water availability. This study was conducted in the seedling nursery of the Department of Plant Sciences at the Federal Rural University of the Semi-Arid (UFERSA). It was adopted a randomized blocks design in subdivided plots, with four blocks. In the plots, the water treatments were placed (irrigated and stressed). The subplots were the plant sages (4, 6 and 8 months). When the plants showed leaf senescence, irrigation was resumed and leaves were selected for biochemical analyzes of photosynthetic pigments, total soluble sugars and total free amino acids were made. At 5 days of water deprivation, the plants had reduced photosynthesis, stomatal conductance and transpiration. At that point, there was a statistical difference for the water potential at noon, pre-dawn, free amino acids and soluble sugars in plants that were subjected to stress. The behavior exhibited by Cryptostegia madagascariensis indicates that this species has a conservative profile, reducing their leaf area and promoting stomatal closure to conserve water